A Galileo Forgery : Unmasking the New York Sidereus Nuncius. - Bredekamp, Horst; Brückle, Irene; Needham, Paul.; Brückle, Irene (Berlin/Boston : De Gruyter, Inc., 2014)
In this work, historians in various fields revise the results presented in the first two volumes of the series, which analyzed the New York copy of Sidereus Nuncius. While many of their findings remain valid, the subject of analysis proved to be a forgery. Volume III describes how the discovery of forgery was made - a watershed moment in the continuing struggle between forgers and those who seek to apprehend them.
Intro -- Introduction -- I Fruitful Doubts 15 May-June 2012 -- II The Evidence of the Forged Printing -- III The Evidence of the Forged Paper -- IV The Evidence of the Forged SNML Sammelband Book Structure -- V The Evidence of the Forged Padua Compasso Book Structure -- VI Results of non-destructive Instrumental Analysis. XRF-, FTIR-Spectroscopy and Microscopy -- VII Towards a Psychology of the Forger -- VIII Final Thoughts -- Photo Credits.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Astronomy -- Early works to 1800.; Galilei, Galileo, 1564-1642.; Jupiter (Planet) -- Satellites -- Early works to 1800.; Electronic books